Ex vivo assessment of neointimal characteristics after drug-eluting stent implantation: Optical coherence tomography and histopathology validation study. (15th October 2016) - Imanaka, Takahiro; Fujii, Kenichi; Hao, Hiroyuki; Shibuya, Masahiko; Saita, Ten; Kawakami, Rika; Fukunaga, Masashi; Kawai, Kenji; Tamaru, Hiroto; Miki, Kojiro; Horimatsu, Tetsuo; Sumiyoshi, Akinori; et al.
Abstract: Background: Optical coherence tomography (OCT) is one of the tools trying to distinguish neoatherosclerosis from other neointimal tissue but its role has to be still validated. This study evaluated the diagnostic accuracy of OCT for characterization of lipid-atherosclerotic neointima following drug-eluting stent (DES) implantation. Methods: Twelve stented coronary arteries from the 7 autopsy hearts were imaged by OCT. These OCT images were compared with histology. By OCT, the morphological appearances of neointima were classified into three patterns: homogeneous pattern, heterogeneous pattern with visible strut, or heterogeneous pattern with invisible strut. Results: Of 21 histological cross-sections, 6 were categorized as homogeneous patterns (29%), 11 as heterogeneous patterns with visible stent strut (52%), and 4 as heterogeneous patterns with invisible stent strut (19%). All homogeneous patterns were composed of smooth muscle cells with collagen fibers. The heterogeneous patterns with visible stent strut included proteoglycan-rich myxomatous matrix and calcium deposition. On the other hand, the heterogeneous patterns with invisible stent strut comprised atheromatous tissue, including a large amount of foam cell accumulation (25%) or large fibroatheroma/necrotic core (75%) inside the stent struts within neointima. The optical attenuation coefficient was highest in the heterogeneous pattern with invisible stent strut due to scattering of light by atheromatous tissue. Conclusion: The heterogeneous patterns with invisible stent strut on OCT imaging identify the presence of lipid-atherosclerotic tissue within neointima after DES. This may suggest the potential capability of OCT based on visualization of stent struts for discriminating atheromatous formation within neointima from other neointimal tissue.